2022
DOI: 10.3390/jcm11020409
|View full text |Cite
|
Sign up to set email alerts
|

Hyperkalemia Following Parathyroidectomy in Patients with Renal Hyperparathyroidism—New Thresholds for Urgent Perioperative Dialysis

Abstract: Parathyroidectomy (PTX) is a mainstay of treating secondary hyperparathyroidism (SHPT) in patients with kidney failure in order to reduce the incidence of cardiovascular events (CVE), increase overall survival and improve quality of life. Perioperative hyperkalemia may lead to devastating cardiac complications. Distinct preoperative thresholds for serum potassium levels (SPL) were defined, but neither their usefulness nor consecutive risks are understood. This study compared the results and efficacy of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Even with the best of our preoperative preparations, we can see that postoperative hyperkalemia can still occur after PTX + AT, and the prevention of postoperative hyperkalemia places a higher demand on our patient management. Bures et al (19) suggested that early postoperative dialysis treatment with assessment of low risk of postoperative complications may be useful in reducing the incidence of postoperative hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Even with the best of our preoperative preparations, we can see that postoperative hyperkalemia can still occur after PTX + AT, and the prevention of postoperative hyperkalemia places a higher demand on our patient management. Bures et al (19) suggested that early postoperative dialysis treatment with assessment of low risk of postoperative complications may be useful in reducing the incidence of postoperative hyperkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of postoperative severe hyperkalemia, urgent dialysis is required to prevent cardiovascular events. The risk factors of hyperkalemia after PTx for SHPT are not well demonstrated, although the relationships of hyperkalemia with gender, age, obesity, and preoperative serum potassium levels are mentioned in small-sized studies ( 107 109 ).…”
Section: Postoperative Complications and Treatmentsmentioning
confidence: 99%
“…Hyperkalemia, an important risk factor for cardiac death in patients treated with hemodialysis, occurs more commonly with a longer hemodialysis-free interval and is exacerbated by fasting prior to surgery . In a study of elective parathyroidectomy in 251 patients treated with hemodialysis, perioperative hyperkalemia (serum potassium level >5.5 mEq/L) occurred in 53% of patients . The stress of surgery combined with the increased hemodialysis-free interval may increase surgical mortality.…”
mentioning
confidence: 99%